Cheated by academia: a review of the status of women in academia - Blanco, Laura Cristina (2023)
The status of women in academia is analyzed through a literature review. The literature shows that important gender gaps persist limiting the promotion and performance of women in academia. In particular, women publish less, are assigned less resources for their research, face higher publishing costs, have less access to networks and their work is less valued, resulting in less citations. Women also tend to receive lower grades in their teaching evaluations compared to their male peers. All of these variables impact their possibilities for promotion and their wages, making it more difficult for them to ascend the academic ladder.